Dopamine in Drosophila: setting arousal thresholds in a miniature brain - Van Swinderen, Bruno (The Royal Society, 2011)
In mammals, the neurotransmitter dopamine (DA) modulates a variety of behaviours, although DA function is mostly associated with motor control and reward. In insects such as the fruitfly, Drosophila melanogaster, DA also modulates a wide array of behaviours, ranging from sleep and locomotion to courtship and learning. How can a single molecule play so many different roles? Adaptive changes within the DA system, anatomical specificity of action and effects on a variety of behaviours highlight the remarkable versatility of this neurotransmitter. Recent genetic and pharmacological manipulations of DA signalling in Drosophila have launched a surfeit of stories—each arguing for modulation of some aspect of the fly's waking (and sleeping) life. Although these stories often seem distinct and unrelated, there are some unifying themes underlying DA function and arousal states in this insect model. One of the central roles played by DA may involve perceptual suppression, a necessary component of both sleep and selective attention.